A note on unique range sets of meromorphic functions with deficient values - Banerje, Abhijit (Tamsui Oxford Journal of Mathematical Sciences)
With the help of the notion of weighted sharing of sets we deal with the problem of Unique Range Sets for meromorphic functions and obtain a result which improve some previous results.